Designing creative teams from creative members: the role of reward interdependence and knowledge sharing. Issue 4 (10th November 2020) - Zhang, Yong; Li, Guiquan; Wang, Mingxuan
Abstract : Purpose: This paper aims to extend understanding of how team creative potential translates into team creativity. Drawing on social exchange theories, the authors propose that reward interdependence produce cooperative intra-team interactions, which in turn enables aggregate levels of individual member creativity to translate into team creativity. Further, the authors propose that reward interdependence enhances this link indirectly by motivating collective norms around knowledge sharing. Design/methodology/approach: Multi-source and multi-wave data was collected from 94 R&D teams in two large medical firms. At Time 1, team members assessed the degree of reward interdependence and knowledge sharing characterizing their team; team leaders rated each member's individual creativity. Unit leaders reported on the team's overall creativity at Time 2 (three months after Time 1). Findings: The results indicate that the effect of aggregate member creativity (AMC) on team creativity is moderated by reward interdependence in such a way that when reward interdependence is high, AMC has stronger positive effects on team creativity. Furthermore, knowledge sharing, as motivated by reward interdependence, mediates this moderating effect. Originality/value: By integrating the team design and team creativity literatures, this paper advances an interactive model in which team creative composition combines with reward interdependence and knowledge sharing to help team creativity.